Assessment of environmental impact of FOOD waste in Turkey - Cakar, Belkis; Aydin, Serdar; Varank, Gamze; Ozcan, H. Kurtulus (ELSEVIER SCI LTD, 2020)
Food waste is a multifaceted problem that has negative impacts on the environment. Life cycle assessment (LCA) is a tool that shows these environmental impacts as quantifiable and is able to interpret the results with an integrated approach. In this study, LCA was used to analyze food waste in Turkey from a bottom up processing perspective. In order to assess the environmental impact of food waste on climatic, water, and energy resources, we calculated the embedded carbon, water, and energy footprints throughout the food supply chain in Turkey. Avoidable food waste was calculated as 16 Mt in Turkey in the year 2016. It is estimated that food waste in Turkey embodied 23.7 Mt of CO2-eq, 6.2 x 10(9) m(3) of water and 13.5 x 10(4) TJ of energy. The results obtained by this research could be used to assess the linkage between food waste and the carrying capacity of resources. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Food waste; Carbon footprint; Water footprint; Energy footprint; Climate change; Life cycle assessment; CARBON; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology